Persistence of Selected Spartina alterniflora Rhizoplane Diazotrophs Exposed to Natural and Manipulated Environmental Variability - Bagwell, Christopher E. (American Society for Microbiology, 2000)
Rhizoplane-rhizosphere nitrogen-fixing microorganisms (diazotrophs) are thought to provide a major source of biologically available nitrogen in salt marshes dominated by Spartina alterniflora. Compositional and functional stability has been demonstrated for this important functional group; however, the quantitative responses of specific diazotroph populations to environmental variability have not been assessed. Changes in the relative abundances of selected rhizoplane diazotrophs in response to long-term fertilization were monitored quantitatively by reverse sample genome probing. Fertilization stimulated Spartina, with plant height nearly tripling after 1 year. Fertilization also resulted in significant changes in interstitial porewater parameters. Diazotrophic activity (acetylene reduction assay) was sensitive to the fertilization treatments and was inhibited in some plots on several sampling dates. However, inhibition was never consistent across all of the replicates within a treatment and activity always recovered. The rhizoplane diazotrophs were quite responsive to environmental variability and to experimental treatments, but none were displaced by either environmental variability or experimental treatments. All strains were detected consistently throughout this study, and extensive spatial heterogeneity in the distribution patterns of these organisms was observed. The physiological traits that differentiate the diazotroph populations presumably support competitiveness and niche specialization, resulting in the observed resilience of the diazotroph populations in the rhizosphere.